Was tun? (Danzig : [s.n.], 1927)
Druk zachęcający do głosowania na Deutschnationale Volkspartei z wyborów 13.11.1927 r.
Keywords: Deutschnationale Volkspartei -- druki ulotne; Wybory -- Polska -- Gdańsk -- 1900-1945 -- druki ulotne; Partie polityczne -- Polska -- Gdańsk -- 1900-1945.; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- źródła; Gdańsk (Polska) -- polityka i rządy -- 1900-1945.